PERAN PERILAKU OCB SEBAGAI MEDIATOR PENGARUH JOB CRAFTING TERHADAP HIGH INVOLVEMENT WORK PRACTICES - Hilda Hadiati; Adi Rahmat; Richa Afriana Munthe (Indragiri Research Center (ingreat), 2025)
Many organizations face the challenge of creating work practices that encourage optimal employee engagement and productivity. One work practice that is considered effective is High Involvement Work Practices (HIWP). The aim of this research is to determine the effect of Job Crafting on High Involvement Work Practices through OCB Behavior as a mediating variable. This research is a type of quantitative research with a causality research design and the population is all State Civil Apparatus and honorary staff at the Community and Village Empowerment Service of Indragiri Hilir Regency. with a sample of 63 people. Data collection techniques using questionnaires and distribution using Google Form. The data analysis tool in this research is Structural Equation Modeling (SEM) which is processed using SmartPLS 3.2.9 for data processing. The results of this research are that Job Crafting has a significant influence on HIWP both directly and through the mediation of OCB behavior.